The correct answer is D.
To transform the graph of y = x^2 to y = -2(x-2)^2 + 2, the following steps need to be taken:
1. Reflect across the x-axis: This will change the sign of y, so the graph will now be y = -x^2.
2. Translate 2 units to the right: This means that the graph will be shifted horizontally to the right by 2 units, resulting in y = -(x-2)^2.
3. Translate up 2 units: This means that the graph will be shifted vertically upwards by 2 units, resulting in y = -(x-2)^2 + 2.
4. Stretch by the factor 2: This means that the graph will be vertically stretched by a factor of 2, resulting in y = -2(x-2)^2 + 2.
Therefore, the correct steps to transform the graph of y = x^2 to y = -2(x-2)^2 + 2 are to reflect across the x-axis, translate 2 units to the right, translate up 2 units, and finally stretch by the factor 2, which is answer D.
Which steps transform the graph of y = x^2 to y = -2(x-2)^2 + 2? (1 point)
A. translate 2 units to the left, translate down 2 units, stretch by the factor 2
B. translate 2 units to the right, translate up 2 units, stretch by the factor 2
C. reflect across the x-axis, translate 2 units to the left, translate down 2 units, stretch by the factor 2
D. reflect across the x-axis, translate 2 units to the right, translate up 2 units, stretch by the factor 2
1 answer